2017
DOI: 10.1038/mp.2017.170
|View full text |Cite
|
Sign up to set email alerts
|

Widespread white matter microstructural differences in schizophrenia across 4322 individuals: results from the ENIGMA Schizophrenia DTI Working Group

Abstract: The regional distribution of white matter (WM) abnormalities in schizophrenia remains poorly understood, and reported disease effects on the brain vary widely between studies. In an effort to identify commonalities across studies, we perform what we believe is the first ever large-scale coordinated study of WM microstructural differences in schizophrenia. Our analysis consisted of 2359 healthy controls and 1963 schizophrenia patients from 29 independent international studies; we harmonized the processing and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
488
9
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(599 citation statements)
references
References 56 publications
(78 reference statements)
71
488
9
2
Order By: Relevance
“…The corona radiata provides the majority of the ipsilateral fibers connections between frontal and motor cortical areas(67). This white matter structure has shown the largest effect size of white matter microstructural deficits in schizophrenia(68) and is also highly heritable(69). It is not clear why this SICI and white matter relationship was strongly mediated by the connections between ipsilateral prefrontal cortex and motor cortex(Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…The corona radiata provides the majority of the ipsilateral fibers connections between frontal and motor cortical areas(67). This white matter structure has shown the largest effect size of white matter microstructural deficits in schizophrenia(68) and is also highly heritable(69). It is not clear why this SICI and white matter relationship was strongly mediated by the connections between ipsilateral prefrontal cortex and motor cortex(Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Lower integrity of cerebral white matter (WM), quantified as reduced fractional anisotropy (FA) of water diffusion measured from diffusion tensor imaging (DTI), is a consistent finding in schizophrenia (Alba‐Ferrara & de Erausquin ; Ellison‐Wright & Bullmore ; Friedman et al, ; Glahn et al, ; Kelly et al, ; Kochunov & Hong ; Kubicki et al, ; Nazeri et al, ; Perez‐Iglesias et al, ; Phillips, Rogers, Barrett, Glahn, & Kochunov, ; Wright et al, ). FA deficits are hypothesized to be prominent in the associative WM fibers and responsible for neuropsychological deficits association with this disorder (Ellison‐Wright & Bullmore ; Friedman et al, ; Kochunov et al, ; Kubicki et al, ; Nazeri et al, ; Perez‐Iglesias et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the impact of regressing the site‐specific methodological variance and advanced denoising approach by comparing the effect size of schizophrenia on regional FA values to those published by the largest meta‐analytic analysis of regional FA deficits to date ( N = 1,984/2,391 patients/controls, thirty independent cohorts worldwide) performed by ENIGMA (Kelly et al, ). The average effect size for regional FA values in ENIGMA was reported to be Cohen's d =∼.25 (Kelly et al, ). This suggested that a sample of N = 250 patients/250 controls is required to detect such an effect size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased densities of the WM neurons not only indicates the experience of developmental insults, but might also disrupt the development of normal connectivity, which may partly underlie the abnormal functions of the brains associated with an increased densities of WM neurons in patients with neuropsychiatric disorders. An intriguing hypothesis is that the altered connectivities associated with the increase in density of WM neurons might underlie the WM abnormalities detected in diffuse tensor imaging studies of schizophrenia patients . This hypothesis should be verified in future studies.…”
Section: What Is the Cause(s) Of The Increased Densities/number Of Wmmentioning
confidence: 95%